Price competition in an inflationary environment - Dürsch, Peter; Eife, Thomas A. (Journal of monetary economics, 2019)
In an experimental study with price-setting firms we find that inflation significantly reduces real prices (by lowering price markups) and significantly raises welfare compared to the treatment with a constant overall price level. Money illusion and a reduced ability to collude in an environment with a constantly changing, i.e., increasing, price level drive this result. In a third treatment with deflation, collusion is somewhat reduced as well, but money illusion pushes prices up so that welfare is lower than under inflation.